2017
DOI: 10.1080/10408398.2016.1211087
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in modified atmosphere packaging and edible coatings to maintain quality of fresh-cut fruits and vegetables

Abstract: Processing of fruits and vegetables generates physiological stresses in the still living cut tissue, leading to quality deterioration and shorter shelf life as compared with fresh intact produces. Several strategies can be implemented with the aim to reduce the rate of deterioration of fresh-cut commodities. Such strategies include low temperature maintenance from harvest to retail and the application of physical and chemical treatments such as modified atmosphere packaging (MAP) with low O and high CO levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 127 publications
(188 reference statements)
0
55
0
Order By: Relevance
“…The lower water vapor transmission correlated with lower weight loss [23], and this can also be seen in the present study. In addition, the higher CO 2 transmission coefficient and lower O 2 transmission coefficient during NSCC coating create a better microenvironment with low oxygen and high carbon dioxide to reduce fruit respiration rate and further delay senescence [24]. Limiting microbial load is also a critical factor to delay senescence and increase the shelf life of the fruits [25].…”
Section: Discussionmentioning
confidence: 99%
“…The lower water vapor transmission correlated with lower weight loss [23], and this can also be seen in the present study. In addition, the higher CO 2 transmission coefficient and lower O 2 transmission coefficient during NSCC coating create a better microenvironment with low oxygen and high carbon dioxide to reduce fruit respiration rate and further delay senescence [24]. Limiting microbial load is also a critical factor to delay senescence and increase the shelf life of the fruits [25].…”
Section: Discussionmentioning
confidence: 99%
“…MAP is one of the world's most recognized preservation methods to maintain the microbial and physicochemical quality of fresh foods . Saxena et al .…”
Section: Introductionmentioning
confidence: 99%
“…MAP is one of the world's most recognized preservation methods to maintain the microbial and physicochemical quality of fresh foods. [8][9][10][11][12] Saxena et al 13 used MAP (3 kPa oxygen (O 2 ), 5 kPa carbon dioxide (CO 2 )) to reduce physiological and quality changes such as respiration rate, texture, and color of fresh-cut jackfruit bulbs at 6 ∘ C during storage. Oms-Oliu et al 14 showed that MAP (2.5 kPa O 2 , 7 kPa CO 2 ) inhibited bacterial, yeast, and mold growth for fresh-cut pear at 4 ∘ C during a storage period of 10 days.…”
Section: Introductionmentioning
confidence: 99%
“…The two main types of MAP are active and passive modification of the atmosphere (Zagory and Kader, 1988). In active MAP, the desired atmosphere is established rapidly by flushing the desirable gas mixture in the package (Ghidelli and P erez-Gago, 2018). In passive MAP, the desired atmosphere is established after a ''lag'' period, as a result of the synergistic effect of the package film permeability and the respiration rate of the commodity (Charles et al, 2008;Lange, 2000).…”
mentioning
confidence: 99%